FINANCIAL PERFORMANCE ANALYSIS USING THE ECONOMIC VALUE ADDED (EVA) METHOD AT PT. TELECOMMUNICATIONS (PERSERO) TBK ON THE INDONESIAN STOCK EXCHANGE FOR THE PERIOD 2017-2022 - Nurfarhana; Akbar, Abdi; Ramli, Anwar; Anwar; Amin, Andi Mustika (Journal Management & Economics Review (JUMPER), 2023)
This study aims to determine the financial performance of PT. Telecommunications Tbk. This type of research is the Quantitative method. The population in this study are all financial statements from 2017-2022. The sample is the balance sheet and income statement. Data collection is done through the method of documentation, namely collecting information about the company PT. Telekomunikasi Tbk, in the form of financial reports through the official website of the Indonesia Stock Exchange. The data analysis technique used is Economic Value Added (EVA) analysis which is obtained from the difference between the NOPAT value and the WACC value. The results of this study indicate that the financial performance at PT. Telecommunications (Persero), Tbk. The period from 2017 to 2022 when measured using Economic Value Added (EVA) obtained positive results, meaning that PT. Telecommunications is able to create added economic value for investors who have invested their capital, and a level of compensation that is higher than the cost of capital. This reflects the company's financial performance in good condition because it has met investors' expectations and has the best financial performance.